Ignition of fuel beds by cigarettes: a conceptual model to assess fuel bed moisture content and wind velocity effect on the ignition time and probability - Viegas, Domingos Xavier (2021)
A conceptual model based on the balance of energy in a system composed of a burning cigarette, ambient flow and a porous fuel bed is proposed to study the burning of a single cigarette and the process of fuel bed dehydration, pyrolysis and its eventual ignition or combustion extinction. Model predictions of time to ignition and of the probability of ignition as a function of fuel bed moisture content and ambient flow velocity are compared with results obtained in laboratory ignition tests of straw fuel beds for various ambient conditions. According to this study, the main parameters influencing the models developed are the fuel bed and tobacco moisture content, as well as the flow velocity.